YouTube dan Pengaruhnya dalam Proses Konversi Menjadi Flat Earther: Studi pada Komunitas Bumi Datar Indonesia - Halimatusa'diah, Halimatusa'diah (Universitas Bina Sarana Informatika, 2021)
ABSTRACT The idea of a Flat Earth in Indonesia became popular along with the development of social media. As one of the most popular social media today, YouTube has the potential to expand the reach of this idea to influence public discourse and recruit followers. This qualitative study aims to analyze the role of YouTube in influencing individual beliefs to convert to being Flat Earthers. The study found that YouTube plays an important role in the process of converting individuals into Flat Earthers. In addition, this study also shows that the claims of religious arguments from this idea, have strengthened individuals to switch beliefs to become Flat Earthers. This religious argument, considered to be in harmony with their holy book. These findings suggest that the YouTube platform has the potential to be a powerful avenue for changing one's beliefs.Â Keywords:Â YouTube, Flat Earth, Conversion, Flat Earthers.Â